Memaknai Profesionalisme Guru Pendidikan Agama Kristen Masa Kini - Ramses Simanjuntak (Sekolah Tinggi Theologia Nazarene Indonesia, 2019)
Professionalism is a word that we often say when we see people working with all the skills and abilities that are qualified accompanied by a sense of full responsibility. Professionalism in work can be found in every profession anywhere, including in the teaching profession. By working professionally, a teacher will prioritize quality performance so that in every job the teacher will be seen as a very noble profession. In relation to Christian Religious Education teachers, Christian Religious Education teachers should carry out their duties with a full sense of responsibility, because they are called to be partners of God in educating the people. The teachers are God's servants who must continue to learn and emulate the Lord Jesus Christ as the Great Teacher who always cares for the people and leads them to the truth.